2016
DOI: 10.1016/j.neuroimage.2016.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Left posterior-dorsal area 44 couples with parietal areas to promote speech fluency, while right area 44 activity promotes the stopping of motor responses

Abstract: Area 44 is a cytoarchitectonically distinct portion of Broca's region. Parallel and overlapping large-scale networks couple with this region thereby orchestrating heterogeneous language, cognitive, and motor functions. In the context of stuttering, area 44 frequently comes into focus because structural and physiological irregularities affect developmental trajectories, stuttering severity, persistency, and etiology. A remarkable phenomenon accompanying stuttering is the preserved ability to sing. Speaking and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
72
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 131 publications
10
72
0
1
Order By: Relevance
“…This study, to the best of our knowledge, is the first to reveal the neural mechanisms underlying the phonological WM deficit in PWS, supporting the ill-developed cognitive-linguistic hypothesis of stuttering (Postma & Kolk, 1993). Specifically, in a phonological WM task that required simultaneous storage and manipulation of syllables, PWS exhibited greater activation in the right inferior frontal gyrus extending to the middle frontal gyrus than fluent controls, consistent with previous findings of increased brain activation in the right hemisphere in PWS (Chang et al, 2009;Fox et al, 1996;Fox et al, 2000;Neef et al, 2016;Preibisch et al, 2003). Post hoc analysis revealed significant negative correlation between the brain activity in the right inferior frontal gyrus and the backward digit span.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study, to the best of our knowledge, is the first to reveal the neural mechanisms underlying the phonological WM deficit in PWS, supporting the ill-developed cognitive-linguistic hypothesis of stuttering (Postma & Kolk, 1993). Specifically, in a phonological WM task that required simultaneous storage and manipulation of syllables, PWS exhibited greater activation in the right inferior frontal gyrus extending to the middle frontal gyrus than fluent controls, consistent with previous findings of increased brain activation in the right hemisphere in PWS (Chang et al, 2009;Fox et al, 1996;Fox et al, 2000;Neef et al, 2016;Preibisch et al, 2003). Post hoc analysis revealed significant negative correlation between the brain activity in the right inferior frontal gyrus and the backward digit span.…”
Section: Discussionsupporting
confidence: 87%
“…Abnormal activity in the right inferior frontal gyrus in PWS has been repeatedly reported in previous functional studies using other paradigms(Chang et al, 2009;Kell et al, 2009;Neef et al, 2016;Neef et al, 2017 ;Preibisch et al, 2003), and it has been thought to represent a compensatory mechanism in response to the left-side impairment(Neef et al, 2017; Abnormal activity in the right inferior frontal gyrus in PWS has been repeatedly reported in previous functional studies using other paradigms(Chang et al, 2009;Kell et al, 2009;Neef et al, 2016;Neef et al, 2017 ;Preibisch et al, 2003), and it has been thought to represent a compensatory mechanism in response to the left-side impairment(Neef et al, 2017; …”
mentioning
confidence: 87%
“…Furthermore, in cases where the FAT was spared from resection, patients experienced no post-operative stuttering. Finally, Neef and colleagues (Neef et al, 2018;Neef et al, 2016) investigated 31 adults with stuttering and 34 controls. They found that more severe stuttering was linked to stronger connectivity of the right FAT, which they interpreted as reflecting an overly active global motor inhibition commonly associated with the right inferior frontal gyrus.…”
Section: Functional Associations Of the Left Frontal Aslant Tract In mentioning
confidence: 99%
“…It has been proposed that the hyperdirect pathway connecting the subthalamic nucleus and RB (inferior frontal gyrus) mediates global response suppression . Therefore, overactivation of this pathway results in increased global inhibition of motor systems, which in turn disrupts control of ongoing and succeeding motor programs for fluent speech . It must also be noted that a recent study revealed altered structural abnormalities in the white matter pathway connecting the right frontal regions with the pre‐SMA, as well as with subcortical structures .…”
Section: Discussionmentioning
confidence: 99%